Implementation Of Intrusion Detection System Using Snort - Al Ghafri, Hamed Hilal; Yusof, Robiah; Zainal Abidin, Zaheera; Kamil, Kurbonov (Faculty Of Information And Communication Technology, UTeM, 2019)
Intrusion Detection System (IDS) is a vital network security tool for protecting the network systems that consists of software and hardware to monitor all the inbound and outbound network and system activities for malicious activities in the network traffic. The purpose of IDS is to assists the network administrator or the system by sending alerts and notifications when there are possible incidents, which violations of computer security policies exist. However, IDS causes a false alarm when attacker perform modifications at the rules settings. Therefore, this study performs experiment to detect anomaly incident and intruder in the network system. The implementation on snort development is provided and testing is executed in order to prove that snort capable to detect intruder. The findings showed that anomaly user can be detected based on port scanning, telnet to port to detect the unusual traffic and monitoring using NMAP to identify abnormal activities. As a result, the impact of Snort could bring an alternative solution on network monitoring in terms of continuous detection on unusual traffic movements, cost effective since Snort is an open source product and it can be customized to suit with the network environment